2016
DOI: 10.1556/1646.8.2016.1.5
|View full text |Cite
|
Sign up to set email alerts
|

An unusual radiological presentation of mucinous adenocarcinoma of the colon

Abstract: Abstract:We report a case of an elderly patient presenting with the left iliac fossa mass. The provisional diagnosis included an infl ammatory diverticular mass or sigmoid colon cancer. Interestingly, computed tomography (CT) of the abdomen and pelvis demonstrated the left incarcerated Spigelian hernia containing an infl amed loop of the colon with signs of an early strangulation. However, at operation, a mucinous tumor was found involving the descending and upper sigmoid colon. The tumor eroded through the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Thus, these findings are not conducive to the early detection and treatment of MAC. [20,21] It has been reported that endoscopic ultrasound (EUS) has a unique advantage for the diagnosis of MAC associated with ascites; EUS frequently identifies ascites missed by other imaging studies, including abdominal CT. This study also demonstrated that EUS-guided paracentesis could identify malignancy in ascetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings are not conducive to the early detection and treatment of MAC. [20,21] It has been reported that endoscopic ultrasound (EUS) has a unique advantage for the diagnosis of MAC associated with ascites; EUS frequently identifies ascites missed by other imaging studies, including abdominal CT. This study also demonstrated that EUS-guided paracentesis could identify malignancy in ascetic patients.…”
Section: Discussionmentioning
confidence: 99%